Penapisan Beberapa Padi Lokal dari Pulau Enggano Terhadap Ketahanan Salinitas - Dwi Astuti; Ade Nena Nurhasanah; Satya Nugroho; Amy Estiati (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2017)
Astuti et al, 2017. Screening of Several Local Rice from Enggano Island to Salinity Tolerance. JLSO 6(2):134-141. Enggano Island, Bengkulu Province, has a lot of local rice germplasm that has been cultivated by people in Enggano Island that is more than 30% as farmer. Identification of local rice from Enggano Island against biotic and abiotic stresses, especially salinity stress is necessary. The identification can be used, among other things, as the information of the local rice planting that related to the rising sea level in Enggano Island which impact on the condition and the area of rice cultivation land, and as a source of finding for resistance genes against salinity stress for improvement of those local rice varieties. Aim of this study is preliminary screening of some local rice from Enggano Island to salinity stress in seed and germination stages. The analysis used Factorial Randomized Design, two factors, the first factorÂ is salt concentration and and the second is local variety. The salt concentrations used were 0 millimolar NaCl, 250 millimolar NaCl, NaCl 275 millimolar and NaCl 300 millimolar and the rice sample used were 11 local rice of Enggano Island, NiponBare varieties as control of rice plants, Pokali as resistant control and IR29Â varieties as susceptible controls. Rice seeds that used in this test are seed in seed stage and germination stage of 10-14 days old. This preliminary screening shows three local genotype of Enggano Island that tolerance to Salinity.